The Effect of Coal Ash As a Sand Substitute on The Compressive Strength of Concrete - Era Agita Kabdiyono; Luthfi Hanafi (Jurnal Teknik dan Science, 2026)
This study aims to analyze the effect of using rock dust as a partial replacement of fine aggregate on the compressive strength of concrete. The substitution variations used were 0%, 30%, and 75% of sand with a concrete design quality of fc' 25 MPa and the mixture planning method refers to SNI 7656:2012. Tests conducted included material characteristics, slump, setting time, and concrete compressive strength at the ages of 7, 14, and 28 days. The results showed that increasing the rock dust content affected the properties of fresh and hardened concrete. The highest slump value was obtained at the 30% variation of 170 mm, while the fastest setting time occurred at the 75% variation of 163 minutes. The results of the compressive strength test showed that normal concrete (0%) had the highest compressive strength of 26.16 MPa at the age of 28 days, followed by the 30% variation of 25.38 MPa, and the 75% variation of 20.37 MPa. Overall, 30% coal dust substitution still produces compressive strength close to normal concrete, while 75% substitution causes a significant decrease in compressive strength.